Seepage Control in Zoned Earth Dams Using Lime–Fly Ash Treated Sandy Soil - Madhloom, Ali M.; Al-Kifae, Abdulaziz A.; Khassaf, Saleh I. (Salehan Institute of Higher Education, 2026)
Seepage control is a critical factor in ensuring the stability of earth dams, particularly those constructed with permeable soils. Uncontrolled seepage and increased pore pressures within the dam body are typically associated with instability, internal erosion, and potential failure. This study aims to evaluate the effectiveness of lime–fly ash mixtures in controlling seepage through earth dams constructed with sandy soil, using experimental modelling and numerical simulation. A physical model of a zoned earth dam was built using untreated sandy soil as the control model, along with treated models in which the sandy core was stabilized with progressively higher lime–fly ash proportions. The results of laboratory permeability tests demonstrated significant reductions in hydraulic conductivity with increasing additive content, resulting in delayed steady-state conditions and a reduction of up to 98.2% in seepage rate compared with the control model. Numerical simulations, validated against experimental results (coefficient of determination, R²>0.98), accurately reproduced phreatic lines and seepage rates and were further used to examine the influence of core slope geometry. The results showed that a core slope of 0.75:1 provided nearly equivalent hydraulic performance to that of the baseline 1:1 slope, offering a more cost-effective alternative. These findings highlight the potential of lime–fly ash–sand mixtures as sustainable and cost-efficient alternatives for dam cores, particularly in regions where clay resources are limited.